A Comparative Study to Determine Functional and Clinical Outcome Differences Between Patients Receiving Outpatient Direct Physical Therapy Versus Home Physical Therapy Followed by Outpatient Physical Therapy After Total Knee Arthroplasty. (November 2016) - Warren, Meghan; Kozik, Jennifer; Cook, Jon; Prefontaine, Paul; Ganley, Kathleen
Abstract : BACKGROUND: Rehabilitation outcomes for patients with total knee arthroplasty (TKA) after hospital discharge are not well understood. PURPOSE: The purpose of this retrospective cohort study was to describe outpatient physical therapy (PT) after TKA and compare short-term (2 months) functional and clinical outcomes of patients following TKA who were discharged from the hospital to home and received (a) outpatient PT immediately (OP) or (b) home health PT before outpatient PT (HH). METHODS: The medical records of 109 men and women postoperative TKA discharged home were abstracted for the 6-minute walk test (6MWT), Knee Osteoarthritis and Outcome Score (KOOS), and knee range of motion (ROM) preoperatively and after discharge from all postoperative PT. Patients received outpatient clinic-based PT immediately after discharge from the hospital (OP) ( n = 87) or home health PT before continued rehabilitation in an outpatient setting (HH) ( n = 22). RESULTS: Despite demographic differences between OP and HH preoperatively, adjusted models revealed no significant differences among KOOS, 6MWT, or knee ROM between OP and HH upon completion of postoperative PT. Patients in OP completed PT on average 20 days sooner ( p = .0007), although the amount of time in outpatient PT ( p = .55) and the number of outpatient PT visits ( p = .68) were similar between groups. CONCLUSION: Gains in function were achieved by patients in OP and HH independent of the postoperative PT setting, although OP achieved gains sooner.